Synthesis and Crystal Structure of Bis[2-((E)-(m-tolylimino)methyl)-6-bromo-4-chlorophenol]copper(II) - Suo, J.L. (Asian Journal of Chemistry, 2011)
A new Schiff base complex CuL2 [HL = 2-((E)-(m-tolylimino)methyl)-6-bromo-4-chlorophenol] is synthesized and characterized using single crystal X-ray diffraction analysis. The crystal belongs to the monoclinic system, space group C2/c, with a = 14.5521 (16), b = 8.6800 (10), c = 21.934 (2) Å, β = 100.0380 (10)°, V = 2728.1(5) Å3, Z = 4, Dc = 1.730 g/cm3, R(int) = 0.0505. The geometry around copper(II) is a flattened tetrahedron. The units of the complex are linked via the weak intermolecular Cu···Cl and Cl···O contracts, leading to the formation of onedimension (1D) chains along the a axis, the multipoint Br···Br intermolecular interactions extend the 1D chain into a 2D (two-dimentional) layer.